The drivers of the substitution of individual services for bundled services: The case of Spain - Alberto Urue\~na López; Covadonga Gijón; Raquel Castro García-Mu\~noz; Olga Ure\~na Fernández; Claudio Feijóo (International Telecommunications Society (ITS), 2015)
In 2007, Spanish telecoms companies began to offer bundled services. Operators started by offering phone plus broadband and phone plus broadband plus pay television bundles, and in doing so, were able to reduce aggregated prices for consumers. In addition to monetary incentives, this study examines the causes that lead consumers (individuals) and households (as economic agents) to replace individual contracts with bundled contracts including more (or fewer) services from those previously subscribed to individually. A model of demand of access to household and individual services was estimated for three services: landline phone, Internet, and pay television using a representative panel of telecoms consumers in Spain. The results show –in decreasing order- the influence of previous experience with particular services, followed by factors related to usage and factors linked with socio-demographic characteristics. Monetary incentives -contrary to common belief- play a significant but minor role.
Keywords: 330; telecoms bundles; substitution; landline phone; broadband Internet; pay tv; triple play; random effects model